Legal Consequences for Notaries Who Include False Information in the Deed of Minutes of the General Meeting of Shareholders - Putri, Pricilia Dwi Anggreni; Gunadi, Ariawan (International Journal Of Economics Social And Technology (IJEST), 2023)
This thesis discusses the legal consequences for a notary who enters a false statement in the Deed of Minutes of the General Meeting of Shareholders, how to place an authentic deed as perfect evidence in the evidentiary system if there is a false statement given by the parties to the Notary. The problems in this thesis are 1) What is the position of an authentic deed as perfect evidence in the evidentiary system if there is false information given by the parties to the Notary; 2) what are the legal consequences for a notary who enters false statements in the Deed of Minutes of the General Meeting. The research method used is normative legal research with the nature of analytical descriptive research. The conclusion from writing this thesis is that the position of the two authentic deeds as perfect evidence in the judicial process with the existence of false information given makes the two authentic deeds underhanded and invalid due to the non-fulfillment of the requirements stipulated in the laws and regulations concerning requirements for the General Meeting of Shareholders (GMS) and conditions for the transfer of rights to shares. So that the legal consequences for a Notary who in carrying out his position is contrary to the Notary's Position Law and the Criminal Code, the notary may be subject to criminal sanctions. This research suggests that the Notary must examine everything needed to make a deed such as all the completeness of the documents from the appearers.